Theoretical approach to the validity of the theory of the four humors in contemporary medicine - Valera, Karla; Rodríguez, Fabio A.; Rodríguez, Orelvis (Revista Gregoriana de Ciencias de la Salud, 2024)
The theory of the four humors laid the foundations for the development of medicine for several centuries. Although contemporary medicine is constantly evolving, any new theoretical construction must have historical support that allows us to determine how the different theories have been perfected. This work aimed to analyze the validity of the theory of the four humors in contemporary medicine. To achieve this objective, a documentary investigation of the literature published in the last two decades was carried out. The theory of the four humors, although superseded by modern science, remains a reminder that there are aspects of health and illness that we still do not fully understand. The scientific advances of contemporary medicine have not completely replaced the importance of clinical observation and understanding of human nature, thus keeping Hippocratic thought current.